Perseverative thinking, threat interpretation bias, and emotional reactivity as mediators between adverse childhood experience domains and psychopathology: A longitudinal mediation study in a cohort of Swiss emerging adults - Brodbeck, J.; Jacinto, S.; Stallmann, L.; Vetsch, N.; Marmet, S.; Neufeld, S. A. (International Journal of Clinical and Health Psychology, 2025)
Adverse Childhood Experiences (ACEs) are robust predictors of negative mental health outcomes and psychosocial difficulties, yet the psychological mechanisms linking ACEs to later psychopathology remain only partially understood. Drawing on a three-wave longitudinal study of Swiss emerging adults (N = 1934), we conducted longitudinal mediation analyses to examine emotional processing (emotional reactivity, perseverative thinking) and social information processing (threat interpretation bias, rejection sensitivity) as pathways from ACEs to psychopathology. Factor analyses identified three distinct ACE domains: family maltreatment, peer victimization, and sexual abuse. By modelling these domains simultaneously, we accounted for their frequent co-occurrence and isolated their unique contributions. Family maltreatment and peer victimization independently were associated with heightened psychopathology and difficulties with emotional processing and social information processing at Wave 1. Furthermore, both adversity domains also predicted persistent elevations in these domains over time, even after controlling for baseline levels and sociodemographic variables. Longitudinal mediation analyses revealed that family maltreatment and peer victimization both predicted psychopathology via perseverative thinking, threat interpretation bias, and emotional reactivity. Sexual abuse, in contrast, showed weaker or delayed associations with psychopathology and operated primarily through threat interpretation bias. Rejection sensitivity, while associated at the bivariate level, did not mediate longitudinal effects. Findings support and extend McLaughlin’s Model of Mechanisms Linking Childhood Trauma to Psychopathology by identifying distinct mediational pathways from specific ACEs to psychopathology. These distinct pathways underscore the relevance of personalized and mechanism-based treatment planning based on the ACEs experienced.